2018
DOI: 10.1097/coc.0000000000000274
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Association Between Radiation Therapy and Survival for Surgically Resected Soft-Tissue Sarcoma

Abstract: High-quality studies reporting adjusted hazard ratios are associated with improved survival in patients receiving radiotherapy for STS. Studies in which odds ratios are calculated from event data and those that do not report adjusted outcomes do not show the same association, likely due to confounding by indication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…To date, no differences were found in overall survival, progression free, or local disease control in case of radiotherapy in soft tissue sarcoma treatment. However, recently a meta-analysis suggested that radiotherapy is associated with lower long-term mortality [14]. In our patient population, 49% of all included patients were additionally treated with neoadjuvant RCT.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no differences were found in overall survival, progression free, or local disease control in case of radiotherapy in soft tissue sarcoma treatment. However, recently a meta-analysis suggested that radiotherapy is associated with lower long-term mortality [14]. In our patient population, 49% of all included patients were additionally treated with neoadjuvant RCT.…”
Section: Discussionmentioning
confidence: 99%
“…A second explanation for why adherence to guidelines had a greater effect on overall survival is that they could actually reflect the direct impact of radiation therapy. Though phase III trials have not shown a survival benefit with radiation therapy, studies that use a larger sample size have shown a survival difference [ 12 , 17 20 ]. Review of the NCDB database reported that the utilization of radiation therapy in the treatment of large, deep, high-grade STS is underutilized and that its use was associated with improved overall survival [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the evaluated treatment, 13 SRs appraised chemotherapy therapies [15, 18, 21, 25-27, 30-32, 37-39]; 5 SRs evaluated radiotherapy interventions [19,22,23,33,36]; 2 SRs assessed surgical interventions [24,34]; 1 SR assessed a combination of surgery (cytoreduction) plus intraperitoneal chemotherapy [28]; and finally 3 SRs assessed a therapy at the forefront named isolated limb perfusion (ILP) [20,29,35].…”
Section: Characteristics and Quality Of Systematic Reviewsmentioning
confidence: 99%
“…SRs [19,32,33,40] were identified with a total of 27 RCTs and 32 observational studies, which addressed three different therapeutic options within this scenario. Two SRs compared different regimens of adjuvant chemotherapy [32,40] mainly based in doxorubicin or doxorubicin plus ifosfamide with surgery.…”
Section: Patients With Localised Resectable Sts (First Line): Fourmentioning
confidence: 99%
See 1 more Smart Citation